AL-‘ULAMĀ’ WARATHAT AL-ANBIYĀ’: Modernity and Nurture of Authority in Aceh Society - Nasution, Ismail Fahmi Arrauf; Miswari, MIswari (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
This paper aims to analyze the immunity factor of Acehnese loyalty to the ulama. Generally, if the ulama fail to respond to problems that arise in modernity, they are abandoned by society. Modernization is taking place very quickly in Aceh. In Aceh, even though the ulama were unable to respond to modernity, they were never abandoned by the community. The type of modernization that is the focus of the author's observation is development, politics, and economics which includes banking and trade. Using a qualitative approach, this study finds, that is in Aceh, precisely because the ulama do not respond to modernity, the immunity of loyalty to the ulama can continue. In Aceh, secular-minded society, they give authority to experts in their respective fields. Because the ulama are treated as religious experts, then when they do not respond to other fields such as development, politics, economics and other fields, they become respected. Although only given space in the field of religion, the position of the ulama remains very important in Aceh because religion is a very important part of the life of the Acehnese people